2018
DOI: 10.1111/his.13700
|View full text |Cite
|
Sign up to set email alerts
|

TFE3 translocation and protein expression in renal cell carcinoma are correlated with poor prognosis

Abstract: Increased TFE3 expression in RCC was associated with poor PFS regardless of the gene translocation status. Moreover, morphological analysis should help to select candidates who would benefit from TFE3 staining and FISH analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 21 publications
(37 reference statements)
4
30
2
Order By: Relevance
“…This is the first comparative analysis, to our knowledge, of PD‐L1 expression in RCC tumours of different types, showing that TRCC exhibited the highest PD‐L1 positivity rate. Our previous study revealed that TFE3 expression in renal cell carcinoma is associated with a poor prognosis . TFE3 translocation is a possible source of immunogenic neoantigen and could stimulate T cell responses.…”
Section: Discussionsupporting
confidence: 90%
“…This is the first comparative analysis, to our knowledge, of PD‐L1 expression in RCC tumours of different types, showing that TRCC exhibited the highest PD‐L1 positivity rate. Our previous study revealed that TFE3 expression in renal cell carcinoma is associated with a poor prognosis . TFE3 translocation is a possible source of immunogenic neoantigen and could stimulate T cell responses.…”
Section: Discussionsupporting
confidence: 90%
“…Conversely, two cases with weak TFE3 expression (1+) had an Xp11 gene fusion. These findings are in line with prior reports of the relatively low specificity and predictive value of TFE3 IHC . TFE3 reactivity could be present in up to 9% of all IHC stained RCC cases detecting not only chimeric TFE3 fusion protein, but also cases with underlying TFE3 amplification and other mechanisms of transcriptional TFE3 activation, and often associated with more aggressive behavior .…”
Section: Discussionsupporting
confidence: 91%
“…Of patients with renal tRCCs, one third are children, one sixth are younger than 50, and 0.6% to 4% are older adults, although adult cases outnumber pediatric cases due the much greater incidence of renal cell carcinoma (RCC) in adults . In addition to affecting younger patients, tRCCs often present as high stage advanced disease and have poor outcomes that are likely similar to that of clear cell RCCs . Accurate diagnosis of tRCC is required for prognosis and guiding clinical management since these tumors are poorly responsive to targeted therapies developed for conventional RCC, but may benefit from novel treatment strategies such as dual PIK3/mTOR inhibition, siRNA‐mediated TFE3 silencing, and MET inhibitors .…”
Section: Introductionmentioning
confidence: 99%
“…1 Approximately one-third patients have metastasis when diagnosed as RCC, 2 so it is urgent to find a new molecular biomarker for RCC diagnosis at the early stage. As reported, genetic biomarkers for RCC have been widely investigated including molecules [3][4][5] and microRNAs (miRNAs). 6,7 miRNAs is a class of endogenous small non-coding RNAs, the length of which is approximately 19-22 nucleotides.…”
Section: Introductionmentioning
confidence: 99%